FREEZING OF DONKEY SEMEN (EQUUS ASINUS) - Frederico Canisso, Igor (2008)
For decades, the development and use of the artificial insemination in the equine, especially with frozen semen, was restricted due to impositions of equine breeders associations that opposed the use of the technique. Recently, these legislations have become more flexible in several countries, allowing the registration of products originating from frozen semen. In Brazil, based on these changes, the main donkey breed association (Brazilian Breeders Association of the Pêga Donkeys) revised their concepts and started to allow the use of this biotechnology. The current interest in many countries for the donkey sire is the production of mules, because their acceptability as these animals inherits suitable characteristics of both donkeys and horses. The first reports on donkey frozen semen used extenders based on egg yolk and glycerol, packed in glass ampoules, and followed the existing methodology for freezing bull semen. However, despite of the elapsed time, few research works have been carried out on this species, especially on semen. This literature review discussed the main techniques of freezing equine semen and describes studies on freezing of sperm of asinine species.